Mathematical modelling of sediment transport dynamics in the Berg River considering current and future water resources development scenarios - Van der Walt, Sarel C. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MscEng)--University of Stellenbosch, 2005.